Incidence of second malignancies after external beam radiotherapy for clinical stage I testicular seminoma - Lewinshtein, Dan; Gulati, Roman; Nelson, Peter S.; Porter, Christopher R. (BJU international, 2012)
Study Type – Harm (case series) Level of Evidence 4 What's known on the subject? and What does the study add? We know that radiation therapy is associated with an increased risk of second malignancies in patients with testicular cancer. However, we know that radiation is being used very commonly in patients with clinical stage I seminoma, despite evidence that it is not required. Moreover, we have now identified which specific second malignancies occur in these patients after radiotherapy. OBJECTIVES • To determine the use of adjuvant external beam radiotherapy (EBRT) for patients with clinical stage I testicular seminoma in the USA. • To quantify the risk of specific second primary malignancies (SPMs) associated with radiation exposure in these patients. PATIENTS AND METHODS • We used the Surveillance, Epidemiology and End Results database to identify patients diagnosed with clinical stage I testicular seminoma between 1973 and 2000. • We evaluated the use of EBRT in these patients. • We calculated standardized incidence ratios of specific SPMs in these patients. • We stratified the incidence of SPMs based on age at seminoma diagnosis and time to SPM from initial seminoma diagnosis. RESULTS • Adjuvant EBRT use declined from the first decade of the study period to the last decade of the study period (80.6% vs 70.2%). • Overall, there was a 19% increase in SPMs in patients exposed to EBRT (observed/expected, O/E, 1.51; 95% CI, 1.08–1.31) compared to the general population. • Specifically, significantly increased risks were observed for thyroid cancer (O/E, 2.32; 95% CI, 1.16–4.16), pancreatic cancer (O/E, 2.38; 95% CI, 1.43–3.72), non‐bladder urothelial malignancies (O/E, 4.27; 95% CI, 1.57–9.29), bladder cancer (O/E, 1.47; 95% CI, 1.01–2.28), all haematological malignancies (O/E, 1.44; 95% CI, 1.08–1.89) and non‐Hodgkin's lymphoma (O/E, 1.77; 95% CI, 1.22–2.48). • Patients had a persistently elevated risk of SPMs 15 years from the time of initial clinical stage I testicular seminoma diagnosis (O/E, 1.29; 95% CI, 1.10–1.49). CONCLUSIONS • We confirmed the increased risk of SPMs after EBRT for seminoma, and we identified the specific types of SPMs that develop. • The risk of EBRT‐associated SPM persists for years after the initial seminoma diagnosis, and patients should be informed about these long‐term risks.